ASPECTS CONCERNING SOME NUMERICAL METHODS FOR APPROXIMATE SOLUTION OF TWO-POINT BOUNDARY VALUE PROBLEMS - POP N., Daniel (Presa Universitară Clujeană, 2015)
The purpose of this work is to determinate the approximate solutions of boundary value problems with conditions inside the interval (0; 1) using collocation method with global B-spline functions of degree k (order k + 1), orthogonal polynomials Tchebychev and combined methods with B-spline functions or C.C method and Runge-Kutta methods. Also using the solver BVP4C we compare this methods for boundary values problems with boundary conditions at in finity.